Contributing Factors of Poor Construction Project Performance in Nigeria - Yahya, Mohd Yamani; Abba, Waziri Abdullahi; Mohamed, Sulzakimin; Md. Yassin, Azlina (International Journal of Property Sciences (E-ISSN: 2229-8568), 2019)
The construction industry has been plagued with problems associated with lack of proper standards and lack of effective project management practice. The complex nature of the industry is what made the construction industry sensitive to poor projects performance. The issue of project performance failure has been left untreated for a very long time and this has caused the tendency for increasing effect on the construction industry and economy. Therefore, the objective of this paper is to identify the factors that contribute to poor construction project performance in Nigeria. The results of this study were achieved through a structured quantitative method of questionnaire distributed to 150 respondents comprising architects, quantity surveyors, civil engineers, and project managers in the Nigerian construction industry. Subsequently, 110 valid responses were retrieved, and the collected data were analysed using Statistical Package for Social Science (SPSS). The findings revealed that fluctuation of materials price, lack of conformance to specification, poor monitoring and feedback, poor contract management and supply of defective material were the most significant factors contributing to poor construction project performance in Nigeria. With these findings, this study has provided the overview to both consultants and contractors towards counteracting the effect of factors associated with poor project performance.